Cross-cultural adaptation and reliability of the Home Falls and Accidents Screening Tool (HOME FAST) in assessing fall-risk home hazards for stroke using technologies over a conventional home visit - Ahmad Ainuddin, Husna; Romli, Muhammad Hibatullah; Hamid, Tengku Aizan; Salim, Mazatulfazura S. F.; Mat Din, Hazwan; Mackenzie, Lynette (John Wiley & Sons, 2022)
Objective. This study is aimed at translating the Home Falls and Accidents Screening Tool (HOME FAST) into the three main languages spoken in Malaysia and investigating its reliability through an alternative technology-based evaluation. Methods. Translation into three languages and cross-cultural adaptation of the HOME FAST was conducted via the five steps adopted from the Mapi Institute. For interrater reliability, occupational therapists who attended a face-to-face home hazard workshop were recruited. Each therapist rated the HOME FAST by using the provided combination of videos and photographs of stroke survivors manoeuvring in their home. For test-retest reliability, the same occupational therapists were invited to rate the same combination of photographs and videos again. Reliability was analysed using Gwet’s AC1 and Bland and Altman’s plot to describe agreement. Results. The translation challenges were minimal and rectifiable. A Bahasa Melayu, Mandarin, and Tamil versions of the HOME FAST were developed. Overall interrater reliability for both video (AC1 = 0.91) and photograph (AC1 = 0.91) were good. The test-retest reliability yielded similar outcome (video: overall AC1 = 0.92 and photograph: overall AC1 = 0.93 ). Conclusion. Using alternative technology (video and photograph) to do a home hazard assessment was feasible. However, the asynchronous nature of these methods has limitations in clarifying certain aspects in the home. Moving forward, potential investigation on other technologies such as telehealth for synchronous and real-time interaction is warranted.